SÍNTESE DE NANOTUBOS DE CARBONO EM MEIO AQUOSO - Kaufmann Junior, Claudir Gabriel (2012)
The nanotechnology has been focused of many studies and become scientifically and technologically revolutionary. It can be found in many products on the market. The nanoscale is defined as a billionth of a meter (10-9m). The manipulation in this scale has provided a series of studies in the health, computing, physics, chemistry, materials and others fields. In the context of manipulation of nanostructures, this paper proposes an alternative produtcion of NTC on arc discharge method, which dispense the use of sealed cameras and working with water as an insulator environment. The project was divided in two main stages: the software development and the production of NTC. A control system via software to manage the approach speed of the electrode (cathode) and the speed of rotation of electrode (anode) was developed in the first stage. In the second stage, tests were performed with different parameters for the production of NTC: source type (direct current and alternating current), type of catalyst, solubilized iron in the water and iron doped in the anode electrode, and also two types of graphite called A and B (higher purity). The material produced was characterized by the Raman Spectroscopy and Scanning Electron Microscopy techniques. Carbon nanotubes were produced when the graphite with higher purity was used, independently of the type of catalyst and the source used. In addition to the CNT was possible to observe with graphite B the production of several carbon nanostructures as nanosphere, nanorods, nanohoneycombs and nanoflowers of grapheme. However the graphite A (low purity) produced microspheres and nanospheres.